An analysis on evaluation of surgical outcomes in zetaplasty for circumferential collapse of velopharynx: a case series - Venugopal, M.; Siddique, S. Mohamed (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Obstructive sleep apnoea syndrome is a disorder that involves periodic partial or total collapse of the pharyngeal airway during sleep which results in progressive asphyxia. It also leads to more insidious conditions including hypertension, diabetes mellitus, coronary artery disease, stroke, cognitive impairment and daytime somnolence. The aim is to analyse the surgical outcomes of series of 16 patients of OSA having circumferential collapse at velopharynx for which Zetaplasty was done by comparing pre-operative and post-operative symptoms, Epworth Sleepiness Scale, DISE and polysomnography. Methods: A prospective study in 16 patients was done in our institute during the period from July 2017 to June 2018 and was followed for a period of 6 months. It comprised of 14 male and 2 female. At the patients in our study had complaints of snoring, frequent awakening at night and excessive day time sleepiness. Results: All the 16 patients showed good improvement in symptoms after the surgery. There was around 50% drop in the post-op AHI. The post-op ESS score was also reduced. Lowest oxygen saturation improved significantly. Conclusions: Zetaplasty for circumferential airway collapse at velopharynx level is a very safe and effective option as determined by the results of our study which is substantiated by reduction in AHI, ESS score and reduction in snoring.